Mikrobiom und gastrointestinale Erkrankungen - Siegel, Julian; Andresen, Viola; Layer, Peter (DMW - Deutsche Medizinische Wochenschrift, 2019)
For some years, microbiome research has become a thriving topic. The most diverse and hitherto poorly understood connections of interactions of the microbiome with the host body (human) seem to play an important role in the genesis of a wide variety of diseases. This article focuses on the importance of the microbiome in gastrointestinal diseases and presents therapeutic approaches.The intestinal microbiome will not be understood completely for a long time due to the highly complex relationships and variety of different microorganisms. The intestinal microbiome is critically involved in the development of diseases, especially in the development of inflammatory bowel disease. Helicobacter pylori infection is a major risk factor for gastric carcinoma. Esophageal microbiome alterations can cause inflammation and decrease the tone of the lower esophageal sphincter. Inflammation is a crucial pathway for tumorigenesis, it can be caused by the “normal” flora and by pathogenic agents. In the microbiome of the colon, interactions of bacteria, viruses and fungi have a very special status. Good oral/dental status protects against pancreatic carcinoma. Fecal microbiome transfer has become more important in the American guideline. Understanding the processes in the intestinal microbiome provides approaches to new therapies that are likely to exceed our current imagination.
Keywords: FMT; CDAD; Pankreaskarzinom; FODMAP; Bakteriophagen